Optimal Ownership Structures in the Presence of Investment Signals - Oliver Gürtler (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2006)
The property-rights approach to the theory of the firm is extended by introducing distorted signals of the parties.investments. Investment incentives are then given in two ways, by allocating ownership rights and by tying pay to the signal realization. Optimal incentive strength, that is, the weight that a signal is optimally given in a wage contract, depends on two distortions, namely the distortion of the signal from the realized and from the disagreement benefit. Under the optimal ownership structure, the deviations of both investments from their first-best levels are relatively small implying that the relative importance of investment matters. Further, it is shown that most of the Grossman-Hart-Moore results are not robust to an introduction of investment signals.
urn:nbn:de:bvb:19-epub-13448-7
Keywords: D2; L2; 330; Signal; Property rights; Integration; Distortion